2016
DOI: 10.1074/jbc.m116.737361
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation Controls Endothelial Nitric-oxide Synthase by Regulating Its Conformational Dynamics

Abstract: The activity of endothelial NO synthase (eNOS) is triggered by calmodulin (CaM) binding and is often further regulated by phosphorylation at several positions in the enzyme. Phosphorylation at Ser 1179 occurs in response to diverse physiologic stimuli and increases the NO synthesis and cytochrome c reductase activities of eNOS, thereby enhancing its participation in biological signal cascades. Despite its importance, the mechanism by which Ser 1179 phosphorylation increases eNOS activity is not understood. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 57 publications
1
13
0
2
Order By: Relevance
“…This implies that a change in FMN domain conformational behavior is needed for CaM to have its kinetic effect on flavin reduction. A recent study showed that CaM speeds the conformational dynamics of nNOSr (16), and this effect, in light of our current results, can explain how CaM could speed flavin reduction in nNOSr but fail to do so in the disulfide-linked CLSS. The disulfide cross-linked CLSS greatly, but not completely, lost its ability to catalyze ET to cytochrome c. We suspect that its residual activity is due to catalysis by the disulfide crosslinked CLSS itself, rather than any contamination by noncross-linked CLSS.…”
Section: And Kinetic Values Derived From the Stopped-flow Absorbance supporting
confidence: 81%
See 2 more Smart Citations
“…This implies that a change in FMN domain conformational behavior is needed for CaM to have its kinetic effect on flavin reduction. A recent study showed that CaM speeds the conformational dynamics of nNOSr (16), and this effect, in light of our current results, can explain how CaM could speed flavin reduction in nNOSr but fail to do so in the disulfide-linked CLSS. The disulfide cross-linked CLSS greatly, but not completely, lost its ability to catalyze ET to cytochrome c. We suspect that its residual activity is due to catalysis by the disulfide crosslinked CLSS itself, rather than any contamination by noncross-linked CLSS.…”
Section: And Kinetic Values Derived From the Stopped-flow Absorbance supporting
confidence: 81%
“…As catalysis continues, the rates of conformational cycling and interflavin ET all contribute to determining the flux of electrons going to cytochrome c during steady-state catalysis. Using this approach, we have studied how conformational behavior controls electron flux through various NOS proteins (10,16,35) and through related dual-flavin reductase enzymes like CPR and methionine synthase reductase. Fig.…”
Section: Impact Of Cross-linking On the Conformational Equilibrium Anmentioning
confidence: 99%
See 1 more Smart Citation
“…Среди механизмов артериальной гипертонии у больных с гиперурикемией в первую очередь обсуждают блокаду продукции оксида азота [14][15][16][17][18][19][20][21][22][23][24], в результате чего снижается его системное вазодилатирующее действие, уменьшаются контроль пролиферативной активности гладких миоцитов стенок артерий и антитромбогенный эффект. Возникающее под влиянием этого повышение общего периферического сопротивления сосудов является мощным фактором активации ренин-ангиотензиновой системы с развитием артериальной гипертонии.…”
unclassified
“…Возникающее под влиянием этого повышение общего периферического сопротивления сосудов является мощным фактором активации ренин-ангиотензиновой системы с развитием артериальной гипертонии. Блокаду синтеза оксида азота у больных с гиперурикемией связывают с гиперпродукцией свободных перекисных радикалов, что, в свою очередь, обусловлено персистирующей субклинической активацией аутовоспалительных механизмов [14][15][16][17][18][19][20][21][22][23][24]. H. Zheng и соавт.…”
unclassified